Treatment of dorsal wrist ganglion cyst by establishing midcarpal volar portal using the “Kiss-in” method - Chen, Bo; Wang, Leining; Liang, Kejiong; Wang, Bing; Jiang, Shuai; Shi, Haifei (Frontiers in Surgery, 2022)
Introduction: This paper introduces the treatment and clinical outcome of the dorsal wrist ganglion cyst utilizing the Kiss-in method to establish the midcarpal volar portal. Materials and Methods: Patients with dorsal ganglia of the wrist (n = 12, 6 females, 6 males) underwent arthroscopic surgery using the Kiss-in method at our hospital between September 2018 and January 2021. All patients underwent pre-operative radiological investigations, such as magnetic resonance imaging (MRI; 12 cases) and/or ultrasonography (12 cases). The mean patients’ age was 30.7 years (range: 19–46 years). The time lost from work, the wrist motion and strength, the presence of scarring, residual symptoms, complications, and recurrence were recorded at a mean follow-up of 10 months. Results: Eleven patients showed a good prognosis with active motion recovery. One patient showed the recurrence of ganglion, and the second arthroscopic resection was performed 5 months after the first surgery for this patient. After the surgery, the patient fully recovered. Conclusions: The establishment of the midcarpal volar portal by the Kiss-in method is safe. The dorsal ganglion cyst resection through the established midcarpal volar portal is a promising approach, allowing the better visualization and broader range motion of the arthroscope.